Indian stock market analysis and prediction using LSTM model during COVID-19. (28th May 2021) - Saravagi, Deepika; Agrawal, Shweta; Saravagi, Manisha
In this study, a computational approach was introduced for predicting the stock prices and statistically analyse the impact of COVID-19 on Indian stock market from 30 January 2020 to 17 July 2020. Long short-term memory model is applied to predict the stock prices of selected companies by comparing the daily stock price movement and returns of various sectors based on historical prices. Results indicate that the stock market fell quickly after the virus outbreak but in the long run, the stock market recovered itself. Finally, we have visualised and compared the predicted values with the actual values. This research helps investors to study the effect of COVID-19 crises at different company's profile and with this analysis, we can assume that in the coming weeks the stock market will recover from the 2020 losses.